Un nuevo sentido encontrado en la praxis cristiana en la moral latinoamericana. La gracia: fundamento y meta de la solidaridad - Rojas Cadena, Leonardo (2023)
Latin American theology remarks, on a contextual way, that spirituality of freedom must be imbued with gratuitousness experience. Communion with the Lord and others in general, is, above all a gift that demands justice. Hence De ahí la universality and radicalism of freedom that he provides. A gift beyond from being considered a passive attitude demands to put it into practice, emerging from a watchman role observing and refl ecting on the different social backgrounds.In order to experience such theological spirit requires become, and commit consciously realistic and determined with the process of liberation of poor and oppressed; not only through generosity but also making a courageous analysis of the current events and accompanying by a plan of action. This is to adopt a political attitude from a perspective of the believer. A transformation means to know and experience. Transformation means a radical change in one’s life, it means to think, feel and live more like Christ, present in a man alienated and who has stripped himself of everything, constructing alternatives or bonds of hope in solidarity.